Microwave Assisted Synthesis and Characterization of Azomethines of Aryl Oxazole - Niraimathi, V.; Jerad Suresh, A.; Latha, T. (Asian Journal of Chemistry, 2011)
2-Chloro N-phenyl acetamide (3) generated by condensation of aniline with chloroacetylchloride in alkali reacts with urea to form phenyl oxazole diamine (5) which on heating under reflux with various aromatic aldehydes forms azomethines of aryl oxazoles (7a-e).